Assessment of Soil Health Indicators Under the Influence of Nanocompounds and Bacillus spp. in Field Condition - Chaudhary, Parul; Chaudhary, Anuj; Bhatt, Pankaj; Kumar, Govind; Khatoon, Hina; Rani, Alka; Kumar, Saurabh; Sharma, Anita (Frontiers in Environmental Science, 2022)
Agricultural yield of major crops is low due to injudicious use of chemical fertilizers in long term agricultural practices which affects soil fertility and biodiversity severely and thereby affecting plant growth. Soil health, regulated by factors like physicochemical properties of the soil, availability of micro/macronutrients, soil health indicator enzymes and microbial diversity is very crucial for agriculture productivity. Thus, it is required to draw attention towards eco-friendly approach which protects the beneficial microbial population of soil. Application of different bioinoculants and agriusable nanocompounds has been reported to enhance soil quality with increased nutrient status and beneficial bacterial population, but additive effects of combined treatments on soil microbial population are largely unknown. The present study investigated the impact of nanozeolite and nanochitosan along with two Bacillus spp. on rhizospheric microbial flora and indicator enzymes to signify soil health under field condition on maize. Soil health was ascertained by evaluating physicochemical analysis, total bacterial counts including N, P and K solubilizing bacteria and soil health indicator enzymes like fluorescein diacetate, alkaline phosphatase, β- glucosidase, dehydrogenase, amylase and arylesterase. Change in copy number of 16S rRNA as a marker gene was used to quantify the bacterial population using quantitative PCR (qPCR) in different treatments. Our study revealed that nanocompounds with Bacillus spp. significantly (P<0.05) enhanced total microbial count (16.89%), NPK solubilizing bacteria (46%, 41.37%, 57.14%) and the level of soil health indicator enzymes up to two-fold over control after 20, 40 and 60 days of the experiment. qPCR analysis showed higher copy number of 16S rRNA gene in treated samples which also indicates a positive impact on soil bacterial population. This study presents a valuable approach to improve soil quality in combined treatments of nanocompounds with bioinoculants and can be used as a good alternative to chemical fertilizers for sustainable agriculture.